A checklist and adult key to the Chinese stonefly (Plecoptera) genera - Chen, Zhi-Teng; Du, Yu-Zhou (Zootaxa, 2018)
The first checklist of the known stonefly genera of China is presented. Using relevant literature and available specimens, a diagnostic key to the ten families representing 65 genera is provided. In addition, illustrations for the key characters are provided.